Two new species of Platymantis (Anura: Ceratobatrachidae) from the Admiralty Archipelago, Papua New Guinea - Richards, Stephen J.; Mack, Andrew L.; Austin, Christopher C. (Zootaxa, 2007)
Two new species of the ceratobatrachid frog genus Platymantis are described from the Admiralty Archipelago, Papua New Guinea. Platymantis admiraltiensis sp. nov. and P. latro sp. nov. have been confused with P. gilliardi Zweifel, 1960 which is known with certainty only from New Britain in the Bismarck Archipelago. Platymantis admiraltiensis sp. nov. differs from P. gilliardi in its much longer legs (TL/SV 0.54–0.60 vs 0.51 in the holotype of P. gilliardi), and from all species of the morphologically conservative P. papuensis complex by its advertisement call, a long series of slowly-repeated ( 0.4–1.9/s) yapping notes lasting up to 44 seconds. Platymantis latro sp. nov. differs from P. gilliardi and all other members of the P. papuensis complex in having a broad dark stripe laterally on the head and an advertisement call consisting of a single biphasic note with 10–20 short, irregularly spaced pulses followed by one long, musical pulse. Both new species are known only from the Admiralty Archipelago. This study confirms the utility of advertisement call structure for distinguishing among morphologically similar ceratobatrachid taxa.